Evaluation of the spring wheat crops development on the base of experimental phenological observations - Рожков, А. О. (Scientific Progress & Innovations, 2012)
The results of four-year researches concerning influence of cenotic factors such as (way of sowing and sowing rates) on the duration of separate development phases of hard spring wheat plants are given. The influence of a cenotic factor characterized by different variations of experimental factors during the interphase periods in plants’ development has been proved in the experiments. Under weakening cenotic stress in row plants sowing and less experimental sowing rates accelerated plants development phases from sowing time to bushing and also during interphase stage from tubing to flowering was observed. With this, the above mentioned variants showed a longer plant development period from full germination to tubing and from flowering to wax ripeness.